Association between polyunsaturated fatty acids and depression in women with infertility: a cross-sectional study based on the National Health and Nutrition Examination Survey - Hong, Yan; Jin, Xia; Shi, Lihong (Frontiers in Psychiatry, 2024)
Background: Identifying possible influencing factors is crucial for the depression symptoms of women experiencing infertility. This study aims to explore the association between polyunsaturated fatty acids (PUFAs) and the odds of depression symptoms in women experiencing infertility.Methods: This is a cross-sectional study based on the National Health and Nutrition Examination Survey (NHANES). PUFA intake was obtained through a 24-hour dietary recall interview. Depression symptoms were defined as Patient Health Questionnaire-9 (PHQ-9) ≥ 10 points or taking antidepressants. The association between PUFA and depression was assessed using a logistic regression model by calculating the odds ratio (OR) with a 95% confidence interval (CI). Subgroup analysis was carried out based on menopausal status and female hormone use.Results: There were 725 participants finally included for analysis. After adjusting the covariables, lower odds of depression symptoms were found in patients with the intake of omega-3 PUFA (OR = 0.48, 95%CI: 0.24-0.96) and omega-6 PUFA (OR = 0.24, 95%CI: 0.14-0.42) in the T2 in comparison to the first tertile (T1). The intake of αlinolenic (ALA) in the T2 (OR = 0.48, 95%CI: 0.23-0.97) and the intake of linoleic acid in the T2 (OR = 0.24, 95%CI: 0.14-0.41) was also found to be related to the reduced odds of depression symptoms in comparison to the first tertile (T1).Our findings suggest a potential association between moderate omega-3 and omega-6 PUFA intake and a reduced risk of depression symptoms in women experiencing infertility. This implies that clinicians might find it useful to consider dietary advice that includes PUFA-rich foods as part of a broader strategy to address mental health in this patient group. However, further research is needed to confirm these preliminary findings and to establish the optimal levels of PUFA intake for mental health benefits.